TEKANAN PADA PENCETAKAN EMPING MELINJO MENGGUNAKAN MESIN PENCETAK SISTEM PNEUMATIK - Sugiyanto, Bambang; Rahman, Abd; Bahri, Nisfan; Supriyanto; Sebayang, Abdi Hanra (JURNAL TEKNOLOGI PERTANIAN, 2023)
ABSTRACT Melinjo chip is a typical Indonesian snack, which is high in nutrition, has a distinctive taste and is liked by many people. The process of producing melinjo chip manually requires a long time, long process, so the productivity is very low, it requires innovation in the procurement and development of equipment/machines for producing melinjo chip so that it can help the production process, lighten the burden on workers/craftsmen and increase the productivity of melinjo chip craftsmen. The research created a prototype of a melinjo chip molding machine, with the application of a pneumatic system to move the pressing tool while providing adequate thrust to flatten the melinjo core seeds in the melinjo chip production process which can replace manual work, the stages involved are designing the machine prototype construction, building machine prototype, tested the machine prototype, the test results showed that to get melinjo chips with a thickness of one millimeter, a pressure of six bars was needed, with four melinjos every once mold and the entire system on the machine could function properly. Keywords: Melinjo chip, pneumatic system, moulding machine Emping Melinjo adalah salah satu makanan ringan khas Indonesia, yang memiliki gizi tinggi, memiliki rasa yang khas dan disukai oleh banyak masyarakat. Proses produksi emping melinjo secara manual membutuhkan proses panjang, lama, sehingga produktifitasnya sangat rendah, perlu inovasi pengadaan dan pengembangan alat/mesin pencetak emping melinjo sehingga dapat membantu proses produksi, meringankan beban pekerja/perajin dan meningkatkan produktivitas perajin emping melinjo. Penelitian menciptakan protipe mesin pencetak emping melinjo, dengan aplikasi sistem pneumatik untuk menggerakkan alat penekan sekaligus memberikan gaya dorong yang memadai untuk memipihkan biji inti melinjo dalam proses produksi emping melinjo yang dapat menggantikan pekerjaan manual, tahapan-tahapan yang dilalui adalah merancang konstruksi prototipe mesin, membangun prototipe mesin, menguji prototipe mesin, hasil pengujian didapatkan bahwa untuk mendapatkan emping melinjo dengan tebal satu milimeter dibutuhkan tekanan sebesar enam bar, dengan empat biji melinjo setiap sekali cetak dan seluruh sistem pada mesin dapat berfungsi dengan baik. Kata Kunci: Emping melinjo, sistem pneumatik, mesin pencetak.